The role of the patent system in stimulating innovation and technology transfer for climate change : including aspects of licensing and competition law - Kim, Hee-Eun (MIPLC studies, 2011)
The world increasingly faces the adverse impact of climate change. What role can intellectual property play to stimulate the necessary innovation and technology transfer? Providing an inventory of patent law, policy and information, including certain private initiatives, this thesis discusses issues at the crossroads of intellectual property and climate change, such as: compulsory licensing for climate change, patent offices' preferential treatment policy for 'green' technology and TRIPS compliance, consideration of 'greenness' in substantive patent law, and antitrust disputes affecting green technology sectors. Just as technical progress on climate change is rooted in a open range of scientific experimentation, intellectual property must offer complementary solutions. Whether through public or private initiative, key among these, the thesis concludes, is the optimal provision of information to technology users. The author has worked at the World Intellectual Property Organization (WIPO) and, in addition to degrees from Ewha Women's University in Seoul and the Munich Intellectual Property Law Center, more recently has obtained an LL. M. in Law, Science & Technology from Stanford Law School.